1997
DOI: 10.1103/physrevc.56.381
|View full text |Cite
|
Sign up to set email alerts
|

Emission of γ rays by x-ray electron-nuclear transitions

Abstract: The X-ray electron-nuclear double transitions (XENDT) are processes in which a transition effected by an inner atomic electron takes place simultaneously with a nuclear electromagnetic transition. We give expressions for the cross sections of electric and magnetic XENDTs of various multipole orders. We calculate the rate of deexcitation of isomeric nuclei induced by XENDTs for the case when the holes in the atomic shells are produced by incident ionizing electrons and find that the induced nuclear deexcitation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The indirect nuclear decay of an isomeric level can be very efficient. This paper is an application of the ideas of Olariu [31][32][33] in a context where it had not been considered previously: a hot plasma where the excitation is ruled by thermal free electrons and LTE atomic levels. The indirect isomer decay process in the plasma is identical in its principle to the two-step ␥-ray transition from isomeric states described by Olariu, where the indirect decay is induced by an intense photon flux at the appropriate energy.…”
Section: B Enhanced Nuclear Decay Of Isomersmentioning
confidence: 97%
“…The indirect nuclear decay of an isomeric level can be very efficient. This paper is an application of the ideas of Olariu [31][32][33] in a context where it had not been considered previously: a hot plasma where the excitation is ruled by thermal free electrons and LTE atomic levels. The indirect isomer decay process in the plasma is identical in its principle to the two-step ␥-ray transition from isomeric states described by Olariu, where the indirect decay is induced by an intense photon flux at the appropriate energy.…”
Section: B Enhanced Nuclear Decay Of Isomersmentioning
confidence: 97%
“…The power levels required by the photon approach to the problem of induced gamma emission studied in this work are comparable to the power levels required by the XENDT approach described in [1]. The choice of isomeric nuclei was restricted in this work by the upconversion condition E γ > 2E ni , and it was restricted to intermediate states of known energy and known spin and parity.…”
Section: Discussionmentioning
confidence: 64%
“…In a recent work it has been shown that the lifetime of isomeric nuclear states can be influenced by X-ray electron-nuclear double transitions (XENDT's), which are processes in which a transition effected by an inner atomic electron takes place simultaneously with a nuclear electromagnetic transition [1]. The rate of deexcitation of isomeric nuclei induced by XENDT's was calculated for the case when the holes in the atomic shells are produced by incident ionizing electrons and it was found that the induced nuclear deexcitation rate becomes comparable to the natural decay rate for ionizing electron fluxes of the order of 10 14 W cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…[3] Electron activated γ-ray sources could also be of interest for Mössbauer experiments in cases where the half-life of conventional radioactive sources is too short to be practical. For example, among the cases listed in Table I Although the cross sections of X-ray electron-nuclear double transitions discussed in [1] and the cross sections for the direct excitation of nuclear transitions are not very large, these processes appear to be of real interest for the development of electron-activated sources of γ-ray photons of narrowly defined energy.…”
mentioning
confidence: 99%
“…It has been shown [1] that if a beam of incident electrons produces holes in the atomic shell of certain atomic species, this atomic excitation can be transferred to the nucleus. The nucleus thus raised in an excited state then decays by the emission of Mössbauer gammaray photons.…”
mentioning
confidence: 99%